Analisis Industri Tekstil Di Jawa Barat Sebelum Dan Setelah Krisis Ekonomi - Alief Anugrah; Hanif Hawari Mohamad; Jenifer Otniel; Muhammad Reza Fahrezi; Muhamad Radian; Farahdinny Siswajanthy (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The textile industry is one of the 10 leading industrial product commodities in Indonesia. This makes the textile industry play an important role in Indonesia, because the textile industry can create jobs, and play a role in meeting clothing needs, and contribute to Indonesia's foreign exchange, as well as encouraging economic growth. Indonesia is a country with an integrated textile industry. Integrated industry involves upstream to downstream industries in producing final products, which include fibers and yarns, fabrics and garments. Indonesia is in seventh place in world exporters of textile products with a contribution of 2.5%. The Indonesian textile industry has quite a lot of internal factors that have the potential to influence competitiveness and need to be resolved immediately effectively and efficiently.